THE SORUS MORPHOLOGY OF FERNS OF THE FAMILY Dryopteridaceae AND THE FAMILY Polypodiaceae THE TATANGGE UNIVERSITY FOREST, SSOTHEAST SULAWESI - Munir, Asmawati; Damhuri; Samai, Suarna; Lisdayanti, Hikma; Lizawarni (BRIN - Badan Riset dan Inovasi Nasional, 2024)
This study aims to determine the morphology of the sorus of ferns (Pteridophyta) Dryopteridaceae and Polypodiaceae families in the Tatangge Education Forest area of Rawa Aopa Watumohai National Park, Southeast Sulawesi. This research involved exploration in the Tatangge University Forest area of Rawa Aopa Watumohai National Park, Southeast Sulawesi to collect samples, then identifying and observing sorus characteristics in the Laboratory of the Biology Education Department, Faculty of Teacher Training and Education, Halu Oleo University, Kendari. The research data were processed and analysed descriptively, regarding the characteristics of the sorus of ferns (Pteridophyta) Dryopteridaceae family including location, shape, colour, and annulus. The results of the study found 5 (five) species of ferns (Pteridophyta) Dryopteridaceae family, and 5 (five) species of Polypodiaceae family that have different sorus characteristics. The Dryopteridaceae family consists of the species Dryopteris celsa, Dryopteris filix-mas, Dryopteris marginalis, Nephrolepis biserrata (Sw) Schoot, and Polistichopsis hasseltii. The family Polypodiaceae consists of the species Drynaria sparsisora (Desv.) T. Moore Pyrrosia longifollia (Burm. f), Pyrrosia lanceolata L Farw, Pyrrosia piloselloides M.G. Price, and Polypodium glycyrriza Licorice Fern.